Islamicjerusalem: A Model for Multiculturalism (American Journal of Islam and Society, 2006)
This paper examines the extent to which `Umar ibn al-Khattab and Salah al-Din adhered to the Islamic vision toward non- Muslims and determines whether they established a multicultural society in Islamicjerusalem after the city’s first and second conquests. In addition, it provides a historical perspective to these two important events, focuses on their attitudes toward Islamicjerusalem’s non-Muslims inhabitants, and investigates whether the Muslims’ understanding of other religions is possible and whether it is an integral part of a pluralist, multicultural society.